Semiotics of Objects in a Modern Kazakhstani Story - Gulbanu K. Tileubay; Bayan U. Joldasbekova; Kuralai O. Tattimbetova (RUDN Journal of Language Studies, Semiotics and Semantics)
New Kazakhstani Russian-language stories require a consistent study: the study analyzes the role of objects in the structure of the plot and in the organization of the art world of the genre of small prose. The aim of the study is to identify semiotic functions of objects in the artistic world of Kazakh realistic narrative using historical-literary, comparative methods, system-typology approach, poetic-structural and stylistic analysis of text. It is established that the objects form the artistic sociology of literary characters. Within this format, objects create a predominantly domestic background in the artistic world of works. In the case of a significant and multilayered extension of semantics, objects contribute to the creation of philosophical and emotional contexts, the re-establishment of conceptual artistic ontology. The images of objects are also used in the process of organizing comparisons and personifications, which serve for organic connection between anthropological and ontological elements. The authors use different forms of personification of the object. In this way, the semantic field of the object is complicated. The object image can be included in the structure of the narrative as an anthropomorphic character. The semiotics of the object in this case is based on cardinal personification. The authors, following the Russian literary classical tradition, consistently use objects to create images of actors.